MESON: A Platform for Optimized Cross-Slice Communication on Edge Computing Infrastructures - Dimitrios Laskaratos; Ioannis Dimolitsas; George Papathanail; Maria-Evgenia Xezonaki; Angelos Pentelas; Vasileios Theodorou; Dimitrios Dechouniotis; Theodoros Bozios; Panagiotis Papadimitriou; Symeon Papavassiliou (IEEE Access, 2022)
In the dawn of the 6G era, evolving service ecosystems raise the need for cross-service interactions. Existing resource/service orchestration frameworks are oblivious to such cross-service interactions, since they tend to orchestrate services independent to each other. In this respect, we stress on the need for optimized cross-service communication, and more specifically, for optimized cross-slice communication (CSC). To this end, we present a CSC orchestration platform, namely MESON, which fulfills all main CSC requirements, such as the discovery of CSC-enabled services, the selection of the most suitable (edge) computing infrastructure, and also the establishment and configuration of CSC in a secure and policy-compliant manner. MESON has been designed and built as an extension of the ETSI NFV MANO framework. Relying on MESON as a proof-of-concept for CSC, we present evaluation results from various performance and scalability tests, and further uncover significant gains from optimized CSC in relation to video streaming and Industry 4.0 use cases.